2015
DOI: 10.1155/2015/848252
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and Residue Level of Thifluzamide in Rice Field Ecosystem

Abstract: An efficient modified QuEChERS method combined with high performance liquid chromatography-tandem mass spectrometry detection (HPLC-MS/MS) was established and evaluated for the residue analysis of thifluzamide in rice grain, husk, straw, seedling, paddy water, and soil. Thifluzamide residues were extracted with acetonitrile, cleaned up with primary secondary amine (PSA), and then determined by HPLC-MS/MS. The fortified recoveries were 76%–106% with RSDs of 3%–13%. The results of the supervised field trials at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Growers rely heavily on the use of various fungicides to control the damage and spread of RSB, which necessitates the use of large amounts of chemical fungicides each year . Thifluzamide (TF) is a broad-spectrum agricultural fungicide that is widely used to control pathogenic fungi such as Rhizoctonia , Ustilago , and Tilletia by inhibiting succinate dehydrogenase in the tricarboxylic acid cycle of the fungus, resulting in fungal death. , However, more than 90% of the pesticide is lost during application due to degradation caused by microorganisms, light, temperature, hydrolysis, and environmental factors such as spray drift and rainfall, and the resulting environmental problems are driving the need for innovative ways to reduce the use of agrochemicals and increase the efficiency of pesticide utilization. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growers rely heavily on the use of various fungicides to control the damage and spread of RSB, which necessitates the use of large amounts of chemical fungicides each year . Thifluzamide (TF) is a broad-spectrum agricultural fungicide that is widely used to control pathogenic fungi such as Rhizoctonia , Ustilago , and Tilletia by inhibiting succinate dehydrogenase in the tricarboxylic acid cycle of the fungus, resulting in fungal death. , However, more than 90% of the pesticide is lost during application due to degradation caused by microorganisms, light, temperature, hydrolysis, and environmental factors such as spray drift and rainfall, and the resulting environmental problems are driving the need for innovative ways to reduce the use of agrochemicals and increase the efficiency of pesticide utilization. , …”
Section: Introductionmentioning
confidence: 99%
“…6 Thifluzamide (TF) is a broad-spectrum agricultural fungicide that is widely used to control pathogenic fungi such as Rhizoctonia, Ustilago, and Tilletia by inhibiting succinate dehydrogenase in the tricarboxylic acid cycle of the fungus, resulting in fungal death. 7,8 However, more than 90% of the pesticide is lost during application due to degradation caused by microorganisms, light, temperature, hydrolysis, and environmental factors such as spray drift and rainfall, and the resulting environmental problems are driving the need for innovative ways to reduce the use of agrochemicals and increase the efficiency of pesticide utilization. 9,10 In recent years, nanotechnology has shown broad application prospects in improving pesticide efficacy, reducing ecotoxicity, reducing biotic stress and increasing plant immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticide contamination of straw may not only affect animal health but also affect human health through the consumption of animal products also containing pesticide residues. On the basis of the results of supervised field trials for pesticide registrations, some pesticide residues in straw were much higher than in harvest grain samples, especially for pesticides that have short preharvest intervals (PHIs). As shown in Table S1 (Supporting Information), maximum residue levels (MRLs) for many pesticides have been set for various types of straw used as roughage.…”
Section: Introductionmentioning
confidence: 99%
“…The previous reports have indicated that the ready mix fungicidal formulations have low risk of resistance development in pathogen due to their broad spectrum and curative action. However, limited information is available on the efficacy of ready mix fungicidal products against sheath blight of rice (Agarwal and , Pal et al 2017) and on their dissipation in rice grains, straw and cropped soil (Kundu et al 2011, Arora et al 2014, Chen et al 2015. Hence, there is a need to study the bio-efficacy and post harvest/terminal residues of new fungicidal formulations to promote international trade and legislation.…”
mentioning
confidence: 99%